Specific Role of the Cyanobacterial PipX Factor in the Heterocysts of Anabaena sp. Strain PCC 7120 - Valladares, Ana (American Society for Microbiology (ASM), 2011)
The PipX factor is a regulatory protein that seems to occur only in cyanobacteria. In the filamentous, heterocyst-forming Anabaena sp. strain PCC 7120, open reading frame (ORF) asr0485, identified as the pipX gene, is expressed mainly under conditions of combined-nitrogen deprivation dependent on the global N regulator NtcA and the heterocyst-specific regulator HetR. Primer extension and 5′ rapid amplification of cDNA ends (RACE) analyses detected three transcription start points corresponding to a canonical NtcA-activated promoter (to which direct binding of NtcA was observed), an NtcA- and HetR-dependent promoter, and a consensus-type promoter, the last with putative −35 and −10 determinants. Activation of pipX took place in cells differentiating into heterocysts at intermediate to late stages of the process. Accordingly, disruption of pipX led to impaired diazotrophic growth, reduced nitrogenase activity, and impaired activation of the nitrogenase structural genes. The nitrogenase activity of the mutant was low under oxic conditions, likely resulting from inefficient protection against oxygen. In line with this, the activation of the coxB2A2C2 and coxB3A3C3 operons, encoding heterocyst-specific terminal respiratory oxidases responsible for internal oxygen removal, was deficient in the pipX mutant. Therefore, the Anabaena PipX factor shows a spatiotemporal specificity contributing to normal heterocyst function, including full activation of the nitrogenase structural genes and genes of the nitrogenase-protective features of the heterocyst.